Effects of topical Ivermectin on imiquimod-induced Psoriasis in mouse model - Novel findings - Sally Ayad Almudaris; Fouad Kadhim Gatea (Pensoft Publishers, 2024)
Aim: investigate the possible anti-psoriatic effect of ivermectin in mice based on observational and histopathological outcomes and biomarkers. Methods: Sixty male Swiss Albino Mice were divided into six groups (Groups I-VI); each group contained ten mice with shaved dorsal skin. The clinical, pathological, and laboratory effects were measured. Results: Topical Ivermectin significantly decreased vascular endothelial growth factor levels. At the same time, the combination of ivermectin plus Clobetasol showed a more significant reduction in tumor necrosis factor-alpha (TNF-α) and Interleukin-17 (IL-17) levels. Regarding the Interleukin-10 (IL-10) level, the Ivermectin and Ivermectin/Clobetasol combination groups showed a significant increase in IL-10. Conclusion: Topical Ivermectin's anti-psoriasis activity increases IL-10 levels and could be used efficiently to alleviate psoriatic symptoms. Its combination treatment with Clobetasol holds promise for the management of psoriasis.